Improving The Islamic Banks Competitiveness Through Efficiency: Two-Stages DEA Analysis - Irman Firmansyah (Islamic Economics Methodology, 2022)
The Islamic banking industry is one of the important factors in economic development so it must have competitiveness to be able to win the competition. Therefore, to have strong competitiveness, the efficiency level of Islamic banks must continue to be optimized. This study aims to determine the efficiency level of Islamic banks and find the factors that influence it by considering internal and external factors. The results showed that only 14.42% of Islamic banks had experienced optimal efficiency even though this study found that efficiency had a positive effect on increasing competitiveness. Important variables that can improve efficiency are age and liquidity. Besides, the board of commissioners also provides its role in managing the level of liquidity to achieve optimal efficiency, but does not play a good role in long-standing banks. In contrast to the sharia supervisory board that has succeeded in carrying out its functions in banks that have long existed to improve efficiency, and vice versa does not play a role in strengthening the level of liquidity to increase efficiency. From external factors, gross domestic product is proven to weaken the relationship between age and liquidity with efficiency.